Dzielmy sie doświadczeniemIs cardiac surgery back-up on-site necessary for percutaneous coronary intervention in patients presenting with acute coronary syndrome? - Pączek, Piotr; Gąsior, Mariusz; Wnęk, Andrzej; Kalarus, Zbigniew; Dydoń, Paweł; Zembala, Marian; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Since Gruenzig first performed PTCA in 1977, use of this procedure has grown tremendously. Because of the new techniques and adjunctive pharmacological therapies the demand for cardiac surgery backup has diminished. In the USA new updated guidelines for PCI (percutaneous coronary intervention) published by the American College of Cardiology (ACC), the American Heart Association (AHA), and the Society for Cardiovascular Angiography and Interventions (CSAI) order the issue of on-site cardiac surgical backup for elective PCI, arguing that performance of PCI without immediate available on-site cardiac surgery potentially compromises patient safety. In Europe guidelines do not even address cardiac surgery back-up. New data confirm the safety and efficacy of primary and elective PCI in patients presenting at hospitals without cardiac surgery on-site.